Predicting secondary school dropout among South African adolescents: A survival analysis approach - Elizabeth H. Weybright; Linda L. Caldwell; Hui (Jimmy) Xie; Lisa Wegner; Edward A. Smith (South African Journal of Education, 2017)
Education is one of the strongest predictors of health worldwide. In South Africa, school dropout is a crisis where by Grade 12, only 52% of the age appropriate population remain enrolled. Survival analysis was used to identify the risk of dropping out of secondary school for male and female adolescents and examine the influence of substance use and leisure experience predictors while controlling for demographic and known predictors using secondary, longitudinal data. Results indicated being male, not living with one’s mother, smoking cigarettes in the past month, and lower levels of leisure-related intrinsic motivation significantly predicted dropout. Results support comprehensive prevention programmes that target risk behaviour and leisure.